THE INFLUENCE OF PEER GROUP SUPPORT ON THE COMPLIANCE OF LIFE-STYLE MANAGEMENT AND DRUG TAKING IN MILD HYPERTENSIVE PATIENTS USING PRE-EXPERIMENT HEALTH PROMOTION MODEL IN COMMUNITY HEALTH CENTER, RUTENG - YOANI MARIA VIANNEY BITA ATY (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Comprehensive management of hypertension will reduce cardiovascular incidence. Peer group support is one method of health promotion that is effective in improving healthy behaviors and improve pain.The purpose of this study was to determine the effect of Peer Group Support for compliance to life-style management and drug taking in patients with mild hypertension using the approach of Health Promotion Model in community health center, at the city of Ruteng, District Manggarai. This study was a pre-experimental study with one-group pretestposttest design. Sample size in this study was 40 patients with mild hypertension. Instruments consisted of a questionnaire, tensimeter, scales and microtoice. Data were analyzed using Anova, linear regression test and paired t-test. The result on the respondents' compliance before and after peer support group obtained t value -25,182 and p 0,000 >0.05 (α). In conclusion, Peer Group Support,may increase hypertensive patient's compliance to life-style management and drug taking.